Understanding the combinatorial thinking through the strategy used by students cognitive reflective in solving permutation - N Aini; D Juniati; T Y E Siswono (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Combinatorial thinking is useful for training students in the concept of enumerationand others. Therefore, it is important to understand the students' combinatorial thinking. Thestrategy were used to be able to know the combinatorial way of thinking. This research aimedto determine the strategy and describe the process of using the strategy of the research subject.The data collection was done by giving the permutation problem and interview. The validationwas done in time triangulation. The technique of data analysis was done through three stepsnamely data reduction, data presentation, and conclusion. The students with reflectivecognitive style were chosen based on MFFT to 140 students. There were 49 students withreflective cognitive style were asked to do the permutation problem. There were two groupsnamely 92% of the students used one strategy and 8% of the students used two kinds ofstrategy. The research subjects chosen were only two students. The results showed that twotypes of strategies used are the filling slot and the formula. The students in general used fillingslot. For convincing the truth, some students used another way that is the formula ofpermutation. Finally, the students matched the answers from the two strategies.